Graduate student experiences and perspectives related to conducting thesis research within long-term ecological projects - Andrea E. Wishart; Melanie R. Boudreau; Allyson K. Menzies (Canadian Science Publishing, 2024)
Long-term ecological research (LTER) projects are considered valuable training grounds for graduate student researchers, yet student voices are largely absent from discussions of LTER merits in the literature. We aimed to identify benefits and challenges encountered by current and former graduate students in conducting graduate research within LTER projects. To explore graduate student experiences and perspectives, we conducted a survey comprising both closed-ended questions (i.e., multiple choice and Likert scale) and open-ended questions. From the responses, we identified emergent categories related to positive and negative experiences using sentiment analysis. We found agreement with purported benefits in areas including networking and access to established field sites and protocols. However, participants also identified data accessibility, authorship decisions, communication, and interpersonal conflicts as significant sources of challenges. We synthesized survey results with existing literature to provide actionable recommendations for principal investigators in four main areas (data, authorship, communication, and management) through an LTER lens. In addition to providing longitudinal data, LTER projects offer graduate students both physical and methodological infrastructure that can serve as the scaffold for new research questions to be developed. However, the likelihood of success of student research, as well as the success of the students themselves, can be improved when the needs of graduate students are prioritized.